Selected Chemical Peat Properties Distribution in Palm Oil Plantation and Its Relationship with Depth Layer and Distance from Mineral Soil Derived From Ultrabasic Rocks: Distribusi Sifat Kimia Gambut di Perkebunan Sawit dan Hubungannya dengan Kedalaman Lapisan Gambut dan Jarak dari Tanah Mineral Berbahan Induk Batuan Ultrabasa - Pulunggono, Heru Bagus; Zulfajrin, Moh.; Hartono, Arief (Jurnal Ilmu Tanah dan Lingkungan, 2020)
Peatland at the research site utilized for oil palm plantation situated alongside with ultrabasic mineral soils. High Mg content in the soil has been reported to inhibit plant growth and distrupt nutrient absorption. Research is aimet to study of pH; Cation Exchange Capacity (CEC); macronutrient of potassium (K), calcium (Ca) and magnesium (Mg); beneficial nutrient of sodium (Na); and micronutrients of iron (Fe), manganese (Mn), copper (Cu) and Zink (Zn) distribution in peat and its relationship with peat depth and distance to ultrabasic mineral soil. The composite of 1,0 kg peat soil samples were collected from the depth of 0 – 30 cm, 30 – 60 cm and 60 - 90 cm toposequently with the distance of 100, 200, 300, 400, 500 and 600 m from the ultrabasic mineral soil. Analysis of peat samples was carried out to determine (i) the contents of K, Ca, Mg, Na extracted by amonium acetate and (ii) the contents of Fe, Mn, Cu, and Zn extracted by DTPA. The result of the study showed that pH value decreased significantly along with increasing peat depth and tended to decrease with increasing distance from mineral soil. CEC content fluctuated and tended to increase along with increasing peat depth and distance from mineral soil. Based on the measurement of Mg and Fe, mineral soil nutrient affected peat to the distance of 600 m from its border. According to Balittanah criteria, peat in the transect area contain high level of available Mg, Na, Fe, Mn, and Zn and low level of K and Ca. Available content of Cu classified as moderate in all depth and distance, except 600 meter and 60 – 90 cm respectively. Beneficial nutrient of Na showed positive correlation with peat depth, indicating marine influence from mineral soil in subsurface. The great disparity between Mg with other cations may disrupt root absorbtion and lead to K and Ca leaching from peat solum.